Development, validation and field evaluation of an indirect ELISA for the detection of antibodies against Brucella abortus in bulk and individual milk samples in dairy cattle - Novoa, María Belén; Aguirre, Nerina; Valentini, Beatriz Susana; Torioni, Susana Marta; Signorini Porchiett, Marcelo Lisandro; Primo, María Evangelina; Elena, Sebastián Alejandro; Vanzini, Victor Rene (Elsevier, 2022)
Brucellosis is an abortigenic and zoonotic disease. In cattle, it is mainly caused by Brucella abortus. The disease is endemic in low- and middle-income countries, being considered a neglected zoonotic disease. In these countries, it is of high importance to develop and validate sensitive, specific and low-cost diagnostic assays for brucellosis. The aim of the present study was the development of an indirect enzyme-linked immune assay (iELISA) to detect anti-B. abortus antibodies in milk samples. We purified the lipopolysaccharide antigen from B. abortus and produced an anti-bovine IgG monoclonal antibody to develop an iELISA (iELISAINTA). The iELISAINTA was validated using 1730 bulk milk samples and 1734 individual milk samples. The sampled dairy herds had at least 3 years of consistency at their positive or negative official brucellosis status. Individual milk samples were taken in parallel with serum samples from the cows. The status of the cows was defined by the result of the complement fixation test (CFT) performed with their serum sample. The reproducibility of the assay was evaluated in two laboratories. In addition, we evaluated the performance of the assay in the field, using 4385 bulk milk samples and 968 individual milk samples. The results of the iELISAINTA were compared with those obtained using the officially accepted brucellosis techniques: iELISA from Canada (iELISACFIA) in milk samples, and the buffered plate antigen (BPA) and the CFT in serum samples. At validation, the sensitivity (Se) of the iELISAINTA in bulk milk samples was 98.61 %, and the specificity (Sp) 98.79 % with a ≥ 10 % of positivity (PP) cutoff. In individual milk samples, the Se was 98.04 %, and the Sp 98.56 % with a ≥ 16 PP cutoff. The chance-corrected agreement kappa value (κ) between the results obtained in the different laboratories was κ = 0.87. In the field evaluation, in bulk milk samples the κ value between the iELISAINTA and the iELISACFIA was κ = 0.86. On individual milk samples, the κ values were: between the iELISAINTA and the iELISACFIA κ = 0.79, between the iELISAINTA and BPA was κ = 0.85, and between the iELISAINTA and CFT κ = 0.82. The developed iELISAINTA showed a very good performance and it could be used as a screening assay for anti-B. abortus antibodies detection in individual milk samples and for epidemiologic surveillance in bulk milk samples.